From Electrochemical Biosensors to Biomimetic Sensors Based on Molecularly Imprinted Polymers in Environmental Determination of Heavy Metals - Malitesta, Cosimino; Di Masi, Sabrina; Mazzotta, Elisabetta (Frontiers in Chemistry, 2017)
Recent work relevant to heavy metal determination by inhibition-enzyme electrochemical biosensors and by selected biomimetic sensors based on molecularly imprinted polymers has been reviewed. General features and peculiar aspects have been evidenced. The replace of biological component by artificial receptors promises higher selectivity and stability, while biosensors keep their capability of producing an integrated response directly related to toxicity of the samples.